Exploring the acute affect of de-coupled batting drills on the gaze behaviour and decision-making of elite baseball players - McCue, M. (University of Ontario Institute of Technology, 2019)
Expert batters utilize context-specific information and gaze behaviour to aid decisionmaking and performance. However, typical practice and warm-up activities often lack relevant context-specific information and visual cues that exist in competition. This study`s purpose was to examine if drills varying in competition representativeness have an acute influence on decision-making and gaze behaviour. Twenty-eight elite baseball athletes participated in one of four warm-up drills and subsequently predicted pitch information in an 18 pitch simulation over three progressively harder temporal occlusion conditions. Main effects of occlusion time, F = 5.43, 3.87; p = .01, .03, and playing level, t = 2.41, p = .02; F = 13.06, p = .003, were observed in decision-making and gaze behaviour analyses, but no statistically significant warm-up condition effects were noted. Players of advanced skill made more correct predictions and fixated on task relevant areas, which was amplified by earlier occlusion times. The lack of a warm-up condition effect may be explained by the athletes` prolonged exposure to unrepresentative practice activities and their subsequent skill in recalibration at switching between tasks.